2019
DOI: 10.1029/2018gb005975
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Cycling of Dissolved Zinc in the Western Arctic (Arctic GEOTRACES GN01)

Abstract: The biogeochemical cycling of dissolved zinc (dZn) was investigated in the Western Arctic along the U.S. GEOTRACES GN01 section. Vertical profiles of dZn in the Arctic are strikingly different than the classic “nutrient‐type” profile commonly seen in the Atlantic and Pacific Oceans, instead exhibiting higher surface concentrations (~1.1 nmol/kg), a shallow subsurface absolute maximum (~4–6 nmol/kg) at 200 m coincident with a macronutrient maximum, and low deep water concentrations (~1.3 nmol/kg) that are homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 130 publications
(239 reference statements)
6
61
0
Order By: Relevance
“…We are unaware of any δ 66 Zn data from dissolved Zn in the Arctic. However, a recent study on Western Arctic dissolved Zn concentrations highlighted a deviation of Zn concentration vertical profiles from the nutrient-type Zn profiles observed in the Atlantic and Pacific 71 . These authors documented higher than global average surface Zn concentrations (~1.1 nmol kg -1 ) with a maximum concentration at 200 m and uniformly lower concentrations in the deep water.…”
Section: Isotopic Contextmentioning
confidence: 93%
See 1 more Smart Citation
“…We are unaware of any δ 66 Zn data from dissolved Zn in the Arctic. However, a recent study on Western Arctic dissolved Zn concentrations highlighted a deviation of Zn concentration vertical profiles from the nutrient-type Zn profiles observed in the Atlantic and Pacific 71 . These authors documented higher than global average surface Zn concentrations (~1.1 nmol kg -1 ) with a maximum concentration at 200 m and uniformly lower concentrations in the deep water.…”
Section: Isotopic Contextmentioning
confidence: 93%
“…These authors documented higher than global average surface Zn concentrations (~1.1 nmol kg -1 ) with a maximum concentration at 200 m and uniformly lower concentrations in the deep water. Jensen et al 71 hypothesises that Western Arctic surface water dissolved Zn originates primarily from incoming Pacific waters that are modified by shelf sediment fluxes from remineralised Zn-rich phytoplankton.…”
Section: Isotopic Contextmentioning
confidence: 99%
“… Cryospheric sampling sites map, U.S. Arctic GEOTRACES GN01 cruise (2015). Relevant ice stations are shown as red dots, and full‐water column stations are shown as smaller black dots (dissolved seawater data found in Jensen et al., 2019 for Zn, Zhang et al., 2020 for Cd, and Jensen, Morton, et al., 2020 for Fe and Mn). Snow, sea ice, and under‐ice seawater samples were collected at Stations 31, 33, 39, 42, 43, and 46, and melt pond samples were taken at these same stations except Station 31.…”
Section: Methodsmentioning
confidence: 99%
“…In the eastern Arctic, subsurface halocline water and eddies are important physical processes to transport materials into basin waters, while in western Arctic, the TPD can directly transport river-influenced shelf water from Siberian shelves toward the center of the basin. Previous studies have shown Siberian shelf-derived 228 Ra, Fe, and Zn was transported by the TPD and found in central Arctic (Jensen et al, 2019;Kipp et al, 2018;Rutgers van der Loeff et al, 2018;Slagter et al, 2017). Enriched dissolved Co, Cu, Ni, and Fe concentrations were also found in the TPD, and the authors argued that organic complexation of those metals, as their speciation study in seawater often shows, can keep them stable and transported over long distances (Bundy et al, 2020;Charette et al, 2020).…”
Section: Transport and Accumulation Mechanismmentioning
confidence: 95%